Postoperative prophylaxis in Crohn's disease after intestinal resection: a retrospective analysis. Issue 3 (1st December 2016) - O'Connor, Anthony; Hamlin, Peter J; Taylor, Jennifer; Selinger, Christian; Scott, Nigel; Ford, Alexander C
Abstract : Introduction: Up to 80% of patients with Crohn's disease (CD) may require surgery at some point in their lives, and it is estimated that as many as 40% may require several surgeries. It has been suggested that prophylactic medication decreases the rate of clinical and endoscopic recurrence following intestinal resection. This study aims to describe real-world clinical outcomes observed from a pragmatic, individualised strategy in postoperative CD. Methods: All patients undergoing intestinal resection for CD between 2009 and 2013 were identified. The endpoint of the study, treatment success, was defined as glucocorticosteroid-free, resection-free survival, at the last point of follow-up, without requiring an escalation or change of therapy during this time. Clinical information was extracted from chart reviews, endoscopy and radiology reports, and from prescribing databases. Patients were followed from the date of surgery, and the last point of follow-up was 31 January 2015. Results: 149 patients were analysed. Median duration of follow-up was 32 months (range 1–69 months). 101 patients received postoperative prophylactic therapy, and 48 did not. In 77 (51.7%) patients, thiopurines were used as first-line therapy, with treatment success occurring in 32 (41.6%) with a median follow-up of 25 months. 11 patients (7.4%) received anti-tumour necrosis factor (TNF)-α monotherapy, with treatment success occurring in 5 patients (45.5%) with a median follow-up of 35 months. 13 (8.7%) patients received first-line combination therapy, with 11 (84.6%) patients achieving treatment success with a median follow-up of 21 months. Conclusions: In our study, combination therapy with anti-TNF-α and immunomodulator therapy was well tolerated, efficacious (efficacy appeared durable for patients with postoperative CD) and superior to monotherapy with either thiopurines or anti-TNF-α drugs. Several limitations notwithstanding, our data suggest that there may be merit in the use of combination therapy in carefully selected postoperative patients whose care has been individualised via a multidisciplinary team meeting format. Prospective, controlled studies are therefore required to further assess the efficacy and safety of combination therapy for postoperative prophylaxis in CD.